Is quality of life measurement likely to be a proxy for health needs assessment in patients with coronary artery disease? - Asadi-Lari, M.; Packham, C.; Gray, D. (2003)
BACKGROUND: The identification of patients' health needs is pivotal in optimising the quality of health care, increasing patient satisfaction and directing resource allocation. Health needs are complex and not so easily evaluated as health-related quality of life (HRQL), which is becoming increasingly accepted as a means of providing a more global, patient-orientated assessment of the outcome of health care interventions than the simple medical model. The potential of HRQL as a surrogate measure of healthcare needs has not been evaluated. OBJECTIVES AND METHOD: A generic (Short Form-12; SF-12) and a disease-specific questionnaire (Seattle Angina Questionnaire; SAQ) were tested for their potential to predict health needs in patients with acute coronary disease. A wide range of healthcare needs were determined using a questionnaire specifically developed for this purpose. RESULTS: With the exception of information needs, healthcare needs were highly correlated with health-related quality of life. Patients with limited enjoyment of personal interests, weak financial situation, greater dependency on others to access health services, and dissatisfaction with accommodation reported poorer HRQL (SF-12: p < 0.001; SAQ: p < 0.01). Difficulties with mobility, aids to daily living and activities requiring assistance from someone else were strongly associated with both generic and disease-specific questionnaires (SF-12: r = 0.46-0.55, p < 0.01; SAQ: r = 0.53-0.65, p < 0.001). Variables relating to quality of care and health services were more highly correlated with SAQ components (r = 0.33-0.59) than with SF-12 (r = 0.07-0.33). Overall, the disease-specific Seattle Angina Questionnaire was superior to the generic Short Form-12 in detecting healthcare needs in patients with coronary disease. Receiver-operator curves supported the sensitivity of HRQL tools in detecting health needs. CONCLUSION: Healthcare needs are complex and developing suitable questionnaires to measure these is difficult and time-consuming. Without a satisfactory means of measuring these needs, the extent to which disease impacts on health will continue to be underestimated. Further investigation on larger populations is warranted but HRQL tools appear to be a reasonable proxy for healthcare needs, as they identify the majority of needs in patients with coronary disease, an observation not previously reported in this patient group